Estimativa de chance para sangramento gengival autorreferido em adolescentes brasileiros, segundo fatores sociodemográficos, marcadores sanguíneos e hábitos de saúde bucal - Carneiro, Tamires Vieira (2017)
INTRODUCTION: Gingival inflammation (gingivitis), which is signaled by bleeding, besides being a risk factor for periodontitis, has also a potential role for cardiovascular diseases in adulthood. OBJECTIVE: To estimate the risks, odds ratio, among Brazilian adolescents, including sociodemographic characteristics, oral health habits and blood markers for the occurrence of self - reported gingival bleeding. METHODS: Secondary data was used from a subsample of 38,069 adolescents who provided blood samples at ERICA (Study of Cardiovascular Risks in Adolescents). The ERICA sample had approximately 85,000 adolescent students from both sexes, in the age group 12 to 17 years old and their data collection took place between 2013 and 2014. In this study, in addition to the description of the data, models were constructed of logistic regression to estimate the chance of self-reported gingival bleeding in adolescents from sociodemographic characteristics, to oral health habits and blood markers, both for Brazil and for the geographical regions. Statistically significant variables were entered into the logistic regression model in the initial selection using the Quisquare test (α = 20%). After this procedure, a more strict level of statistical significance was adopted (α = 5%), and only the variables that showed significance were shown in the results. The analyzes were done in STATA (version 14.2). RESULTS: Considering the total sample (Brazil), the main statistically significant factors to estimate the odds of adolescent gingival bleeding were: female (OR 1.56 95%CI 1.39-1.79) (compared to gender male), age range of 15-17 years (OR 1.25 95%CI 1.08-1.44) (compared to 12 to 14 years), black color (OR 1.27 95%CI 1.04-1,56) or brown (OR 1.23 95%CI 1.06-1.43) (compared to white), daily tooth brushing only once a day (compared to two, three and more than three times (OR 1,56 95%CI 1.08-2.27, OR 1.89 95%CI 1.30-2.70 and OR 2.27 95%CI 1.61-3.23, respectively), and did not use dental floss (OR 1,18 95%CI 1.03-1.35) (compared to the ones that use them) .With regard to Logistic Regression models for each geographic region, some variables that were significant in the Brazil model were not for the regional models. that were significant in the Brazilian model presented significant in regional models. CONCLUSIONS: It was observed that 50.16% were female and the most commonly reported color was brown (48.06%). A percentage of 53.40% was in the age range of 15 to 17 years. Of the adolescents surveyed, 17.94% reported having gingival bleeding. Regarding oral health habits, almost half of the adolescents reported having gone to the dentist less than 6 months ago (49.04%). The most frequent number of brushings was 3 times (44.59%). A portion of 47.41% referred not to use dental floss in oral hygiene. The majority of patients presented desirable levels of LDL (76.97%), Triglycerides (80.20%), Total Cholesterol (55.64%), HDL (53.17%), Insulin (87.53%) and Glycemia, 85%). As for inferential analysis, being female, between 15 and 17 years of age, black or brown, brushing once a day and not using dental floss increased by at least 4 times the chance of referring to the presence of gingival bleeding in Brazilian adolescents. When dividing the sample by regions, it was found that, for adolescents from the North region, being female, of black color and not using floss in oral hygiene, increased the chance of reporting gingival bleeding in 2.37 times. For the Northeast region, not using dental floss in oral hygiene increased the chance of referring gingival bleeding by 1.32 times. In the Southeast region, being female, aged 15 to 17 years and brushing only once a day, increased the chance of gingival bleeding in 4.31 times. For the South region, being female and doing brushing only once a day increased the chance of gingival bleeding by 6.59 times. As for the Midwest region, being female and not using dental floss in oral hygiene increased the chance of referring to gingival bleeding in 2.31 times. The blood markers evaluated showed no association with self-reported gingival bleeding. Therefore, their chance can be estimated from sociodemographic factors, as well as factors related to oral health, but according to the methodology used in this study, there was no evidence that gingival bleeding is associated with lipid metabolism or serum changes in Brazilian adolescents.